An Experimental Review on Elliptic Flow of Strange and Multistrange Hadrons in Relativistic Heavy Ion Collisions - Shusu Shi (Advances in High Energy Physics)
Strange hadrons, especially multistrange hadrons, are good probes for the early partonic stage of heavy ion collisions due to their small hadronic cross sections. In this paper, I give a brief review on the elliptic flow measurements of strange and multistrange hadrons in relativistic heavy ion collisions at Relativistic Heavy Ion Collider (RHIC) and Large Hadron Collider (LHC).